Cognitive Attachment Model of Voices: Evidence Base and Future Implications - Berry, Katherine; Varese, Filippo; Bucci, Sandra (Frontiers in Psychiatry, 2017)
There is a robust association between hearing voices and exposure to traumatic events. The identification of mediating psychological mechanisms for this relationship is fundamental to theories of voice-hearing, and the development of treatments for distressing voices. This paper outlines the Cognitive Attachment model of Voices (CAV), a theoretical model to understand the relationship between earlier interpersonal trauma and distressing voice-hearing. The model builds on attachment theory and well-established cognitive models of voices and argues that attachment and dissociative processes are key psychological mechanisms that explain how trauma influences voice-hearing. Following the presentation of the model, the paper will review the current state of evidence regarding the proposed mechanisms of vulnerability to voice-hearing and maintenance of voice-related distress. This review will include evidence from studies supporting associations between dissociation and voices, followed by details of our own research supporting the role of dissociation in mediating the relationship between trauma and voices and evidence supporting the role of adult attachment in influencing beliefs and relationships that voice-hearers can develop with voices. The paper concludes by outlining the key questions that future research needs to address to fully test the model and the clinical implications that arise from the work.